Recent advances in the management of Thalassaemia: A Review Update - Sarker, Nihar Ranjan; Ghosh, Ashis Kumar; Saha, Santosh Kumar; Shahriar, Abdullah (Journal of Shaheed Suhrawardy Medical College, 2017)
The discussion of disease management focuses on the use of transfusion therapy and the newly developed oral iron chelators, deferiprone and deferasirox, especially combination of the chelator drugs. It has been also discussed on splenectomy and pediatrician management of endocrinopathies and cardiac complications. In addition, the use of hematopoietic stem cell transplantation has produced cure rates as high as 97%, and the use of cord blood transplantation as well. Major advances have being made in the discovery of critical modifier genes, such as Myb and especially BCL11A (B cell lymphoma 11A), a master regulator of HbF (fetal hemoglobin) and hemoglobin switching. Finally, the year 2010 has brought in the first successful experiment of gene therapy in a ß-thalassemia patient, opening up the perspective of a generalized cure for all ß- Thalassaemia patients. J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 31-37